2013
DOI: 10.1007/978-3-642-41190-8_36
|View full text |Cite
|
Sign up to set email alerts
|

SVM-Based Classification of Class C GPCRs from Alignment-Free Physicochemical Transformations of Their Sequences

Abstract: Abstract. G protein-coupled receptors (GPCRs) have a key function in regulating the function of cells due to their ability to transmit extracelullar signals. Given that the 3D structure and the functionality of most GPCRs is unknown, there is a need to construct robust classification models based on the analysis of their amino acid sequences for protein homology detection. In this paper, we describe the supervised classification of the different subtypes of class C GPCRs using support vector machines (SVMs). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 13 publications
5
17
0
Order By: Relevance
“…A batch of previous supervised classification experiments using SVMs were the starting point for these [9]. Such experiments involved an iterative 5 cross-validation (CV) process, splitting the dataset into 5 randomly stratified folds where 4 folds were used for the construction of the model and the remaining one to evaluate the classification results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A batch of previous supervised classification experiments using SVMs were the starting point for these [9]. Such experiments involved an iterative 5 cross-validation (CV) process, splitting the dataset into 5 randomly stratified folds where 4 folds were used for the construction of the model and the remaining one to evaluate the classification results.…”
Section: Resultsmentioning
confidence: 99%
“…Recent analysis using semisupervised and supervised classification of class C GPCRs [8,9] with this type of transformation showed that overall accuracy (the ratio of correctly classified sequences) reaches an upper bound in the area of 90% that it is not significantly increased when more sophisticated physico-chemical transformations of the sequences are applied.…”
Section: Introductionmentioning
confidence: 99%
“…The amino acid sequences of varying lengths were first transformed into fixed-size feature representations. For this, we used in previous work transformations based on the physicochemical properties of the sequences [8]. Instead, in this work we use short protein subsequences in the form of n-gram features.…”
Section: Methodsmentioning
confidence: 99%
“…This paper specifically focuses on the class C subset of a publicly available GPCR database. These data were analyzed in a previous study [8] using a supervised, multi-class classification approach that yielded relatively high accuracies in the discrimination of the seven constituting subtypes of the class. This previous work used several transformations based on the physicochemical properties of the sequence amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…The data in the following experiments were extracted from GPCRDB Previous research [20] investigated the supervised classification of these data sequences, from several of their alignment-free transformations, including AAC, digram, and ACC, among others. Here, we use K-Means and FCM to investigate to what extent the natural clustering structure of the data fits the subfamilies (classes) description.…”
Section: Materials and Experimental Settingmentioning
confidence: 99%